2018
DOI: 10.1002/advs.201800502
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formed Protective Barrier Enabled by Sulfur@Titanium Carbide (MXene) Ink for Achieving High‐Capacity, Long Lifetime Li‐S Batteries

Abstract: Sulfur (S) is an attractive cathode material with advantages including high theoretical capacity and low cost. However, issues such as the lithium polysulfide shuttle effect and its insulating properties greatly limit the future applications of lithium‐sulfur (Li‐S) batteries. Here, a viscous aqueous ink with nanoscale S uniformly decorated on the polar, metallically conductive titanium carbide MXene nanosheets (S@Ti3C2Tx) is reported to address these issues. Importantly, it is observed that the conductive Ti3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(178 citation statements)
references
References 61 publications
6
162
1
Order By: Relevance
“…Following exfoliation, hydrous RuO 2 nanoparticles were deposited in situ on the Mxene nanosheets by admixing a RuCl 3 solution into a well-dispersed MXene suspension. [29,30] These interactions effectively limit the self-growth and spontaneous agglomeration of RuO 2 ·xH 2 O, [31,32] resulting in monodispersed RuO 2 nanoparticles decorated on the nanosheets. [29] Following deposition of the Ru ions, hydrous RuO 2 nanoparticles were subsequently formed through oxidation of the Ru 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Following exfoliation, hydrous RuO 2 nanoparticles were deposited in situ on the Mxene nanosheets by admixing a RuCl 3 solution into a well-dispersed MXene suspension. [29,30] These interactions effectively limit the self-growth and spontaneous agglomeration of RuO 2 ·xH 2 O, [31,32] resulting in monodispersed RuO 2 nanoparticles decorated on the nanosheets. [29] Following deposition of the Ru ions, hydrous RuO 2 nanoparticles were subsequently formed through oxidation of the Ru 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…By utilizing the conversion type materials (such as sulfur, S) and fabricating Li‐S batteries, the capacities and energy densities can be much improved. The layered conductive MXenes can be used either as efficient hosts for accommodating a high amount of sulfur, or a protective membrane to suppress the shuttle effect of polysulfides (LiPSs) . Besides, MXene nanosheets also possess a high aspect ratio, rendering a good flexibility which can be used as conductive binder for these battery materials and maintain the mechanical stability of the electrodes.…”
Section: Application In Other Types Of Esdsmentioning
confidence: 99%
“…However, in that report, a large amount of TiO 2 was found in the X‐ray photoelectron spectroscopy (XPS) of Ti 2 C‐S composites, rendering it is difficult to tell if the suppressed LiPSs shuttle effect is due to the intrinsic surface of MXene or because of the as‐oxidized TiO 2 , since the latter has been shown to be effective in retarding the LiPSs diffusion process . Alternatively, Zhang et al reported a S@Ti 3 C 2 T x composite viscous ink which can be directly casted onto Al foil (and other various substrates) as the cathode. The Ti 3 C 2 T x flakes in the obtained S@Ti 3 C 2 T x films were continuously cross‐linked to each other and efficiently wrapped the S nanoparticles uniformly (Figure b) .…”
Section: Application In Other Types Of Esdsmentioning
confidence: 99%
See 2 more Smart Citations